Pricing currency risk in the stock market: Empirical evidence from Finland and Sweden 1970-2009 - Jan Antell; Mika Vaihekoski (Aboa Centre for Economics (ACE), 2011)
We investigate the role of currency risk on stock markets in two interlinked Nordic countries exhibiting a gradual move from fixed to floating exchange rates. We apply the Ding and Engle (2001) covariance stationary specification in a multivariate GARCH-M setup to test a conditional international asset pricing model. Using a sample period from 1970 to 2009, we find that the currency risk is priced in both stock markets as well as the price to be lower after the flotation of the currencies. We also find the cross-country exchange rate shock from Finland to affect the price of currency risk in Sweden, but not vice versa. Finally, we discuss some of the potential issues in applying multivariate GARCH-M specifications in tests of asset pricing models.
Keywords: G12; G15; 330; conditional; international asset pricing model; currency risk; devaluation; multivariate GARCH-M; Finland; Sweden